A cross-sectional and longitudinal cohort study of creatinine-to-cystatin C ratio and cardiovascular disease risk in a middle-aged and elderly population - Yuling Chen; Yuling Chen; Fengmin Xu; Jia Li; Yixi Bao (Frontiers in Endocrinology)
BackgroundThe creatinine-to-cystatin C ratio (CCR) has recently been proposed as a proxy indicator for sarcopenia. It has been linked to a range of adverse outcomes. However, the relationship between the CCR and cardiovascular disease (CVD) is not widely recognized. This study used data from the China Health and Retirement Longitudinal Study to investigate the association between the CCR and CVD in a middle-aged and elderly population.MethodsThe cross-sectional study and longitudinal cohort study included 10,614 and 6,720 passengers, respectively. The occurrence of CVD incidents was defined as self-reported health history or receipt of cardiac disease treatment. The CCR through creatinine (mg/dL) and cystatin C (mg/dL) were calculated and grouped by quartiles. Unadjusted and adjusted logistic regression models were employed to further explore the CCR-CVD relationships.ResultsThe findings of our study demonstrated a progressively significant reduction in the risk of CVD with an additional CCR. The cross-sectional cohort findings indicated a 21% reduction in the risk of CVD with every additional unit of CCR (OR=0.79, 95% CI, 0.73-0.84). In three logistic regression models, there was a significant association between CCR quartiles and a lower risk of CCR (p for trend <0.001). Further subgroup analyses revealed a 16% reduction in the incidence of CVD with each additional unit of CCR among individuals aged below 65 years (OR, 0.84; 95% CI, 0.78–0.91) and a 18% decline in CVD with each unit of CCR in married populations (OR, 0.82; 95% CI, 0.77–0.88). The findings of the Longitudinal Cohort Study indicated that for each unit increase in CCR, there was an 22% reduction in the risk of CVD (OR=0.78, 95% CI, 0.68-0.90). In logistic regression models adjusted for all co-dependent variables, the prevalence of CVD was reduced by 15%, 21%, and 41% as the number of CCR quartiles increased. This result was also verified by restricted cubic spline analysis.ConclusionIn conclusion, the correlation between an elevated CCR and a reduced risk of CVD in middle-aged and elderly populations has been established. Enhanced CCR levels may prove useful in predicting CVD occurrence in the elderly, thus representing a simple and effective biomarker.